Mengungkap Efektivitas Inovasi Layanan Samsat Terhadap Kepatuhan Wajib Pajak: (Studi Kasus di Kantor Bersama Samsat Badung) - I Komang Triana Utama Yasa; Nyoman Ayu Wulan Trisna Dewi (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to determine 1) The form of application of Gelis services in Badung Regency, 2) Motor vehicle taxpayers' responses to Gelis services in Badung Regency, 3) The effectiveness of Gelis services to motor vehicle taxpayer compliance in Badung Regency.The approach used in this study is qualitative. The data collection methods carried out in this study were observation, interviews and documentation studies. Meanwhile, the data analysis techniques used in this study include data reduction, data presentation, and data inference. The results showed 1) The form of implementing this service is by using the SOP that has been set at the Samsat Badung Joint Office. 2) Taxpayer responses to such services are relatively positive in terms of service quality and promotion to improve taxpayer compliance, but there are obstacles in the aspect of clarity of instructions. 3) Gelis service innovation is very effective in increasing motor vehicle tax revenue in Badung Regency. This can be seen from the effectiveness ratio value which shows the figure of 119%, which has exceeded the effective criteria (90-100%). The increase in motor vehicle tax revenue in Badung Regency after the implementation of the Drive Thru system shows that this innovation is able to increase the compliance of motor vehicle taxpayers in Badung Regency.